EFEKTIVITAS PENERAPAN MODEL RECIPROCAL TEACHING UNTUK MENINGKATKAN KETERAMPILAN BERBICARA PADA PELAJARAN BAHASA INDONESIA KELAS V SDN 09 RANGKANG - madelen; Felisitas Victoria Melati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This model. It used Classroom Action Research (CAR) as a way to solve problems related to learning issues in the classroom. The research was done in two parts, and each part had four steps: planning, doing, watching, and thinking. If a part didn't give the results they wanted, they would do it again with the same steps, using the Reciprocal Teaching method. They looked at the data by describing it using simple math methods. Before the parts started, students didn't speak very well. Only 30% (7 out of 25 students) met the Minimum Mastery Criteria (MMC) of 70. In Cycle I, there was a noticeable improvement. The average speaking score increased to 75.2, a 12.7-point gain from the pre-cycle, and 60% of students (15 students) met the MMC. The most evident progress was seen in students’ confidence and sentence variation, though fluency and vocabulary accuracy still needed development.Improvements continued in Cycle II, with the average score rising to 85.1—an additional increase of 9.9 points from Cycle I and 22.6 points from the pre- cycle. The percentage of students who met the MMC jumped to 90%, exceeding the minimum success indicator of 75% class mastery. Students also showed better fluency, vocabulary use, and the ability to express ideas systematically. The teacher’s involvement was a contributing factor to these outcomes. In general, the study found that Reciprocal Teaching really helps students improve their speaking skills when learning Indonesian, especially when talking about single and mixed objects.